2020
DOI: 10.1177/0021998320975445
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of mechanical and tribological properties of carbon fiber reinforced composites via chemically grafting MA onto MnO2 nanosheets as interphase

Abstract: To intensify the interfacial properties between carbon fiber (CF) and resin without sacrificing fiber, a new type of carbon fiber reinforced resin composite was designed and fabricated with MnO2 nanosheets and melamine (MA) as interphase. The MnO2 nanosheets were uniformly grown on the carbon fiber via hydrothermal method. And then MA was grafted on the MnO2 nanosheets to from chemical bond with resin by a simple bath shock method. The experiment results show that the flexural and tensile strength of the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…50 According to Fei et al, the flexural, tensile, and frictional characteristics of the carbon fiber-reinforced resin were enhanced by synergetic reinforcement in the mechanical interlocking and chemical bonding of MnO 2 nanosheets and melamine. 51 El-Nemr et al used acrylonitrile-butadiene rubber composites to incorporate different concentrations of MnO 2 and iron oxide. 52 The addition of MnO 2 to the rubber matrix improved the tensile strength and hardness of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…50 According to Fei et al, the flexural, tensile, and frictional characteristics of the carbon fiber-reinforced resin were enhanced by synergetic reinforcement in the mechanical interlocking and chemical bonding of MnO 2 nanosheets and melamine. 51 El-Nemr et al used acrylonitrile-butadiene rubber composites to incorporate different concentrations of MnO 2 and iron oxide. 52 The addition of MnO 2 to the rubber matrix improved the tensile strength and hardness of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…For this, the rubbing counterpart can readily penetrate, scratch and tear the surface resin of the sample, making many large pieces of resin be peeled off the bulk sample. As a result, the abrasive dust produced during the friction process is rich and the transfer film between the sample and counterpart cannot be well completed, failing to prevent the sample from sequent abrasive damage 61 . However, as the PANI@NiPS heterostructures are introduced and dispersed evenly in the EP matrix, the scattered fillers can share much additional stress to enhance the load‐bearing capacity of EP composites significantly, avoiding the early breakage caused by stress concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Another study revealed that the addition of 30 wt.% CF to the composite resulted in inferior dispersion and greater stress concentrations in the matrix, which promoted detachment of fillers and degraded the tribological performance of the CF/PA6 [11]. Many attempts have focused on fiber modification to improve the interfacial interaction between carbon fiber and polymer matrix [12][13][14]. However, the enhancement of CF modifications is limited by the potential impacts of compromising the strength of CF itself or complicating the preparation process.…”
Section: Introductionmentioning
confidence: 99%